Influence of temporary organic bond nature on the properties of compacts and ceramics; AIP Conference Proceedings; Vol. 1698 : Advanced Materials in Technology and Construction, AMTC-2015 - Ditts A. A. Aleksander Andreevich; Revva I. B. Inna Borisovna; Pogrebenkov V. M. Valery Matveevich; Galashov E. N. Evgeny Nikolaevich; Nepochatov Yu. K. Yury Kondratjevich; Kosolapov A. A. Artem Anatoljevich (2016, 2016)
Title screen